An investigation of sound absorption coefficient on sisal fiber poly lactic acid bio-composites - Jayamani, E.; Sinin, Hamdan; Rahman, M.R.; Bakri, Abdul Karim; Kakar, A. (John Wiley and Sons Inc., 2015)
In this research, the mechanical, acoustical, thermal, morphological, and infrared spectral properties of untreated, heat and alkaline-treated sisal fiber-reinforced poly-lactic-acid bio-composites were analyzed. The bio-composite samples were fabricated using a hot press molding machine. The properties mentioned above were evaluated and compared with heat-treated and alkaline-treated sisal fibers. Composites with heat-treated sisal fibers were found to exhibit the best mechanical properties. Thermo-gravimetric analysis (TGA) was conducted to study the thermal degradation of the bio-composite samples. It was discovered that the PLA-sisal composites with optimal heat-treated at 160°C and alkaline-treated fibers possess good thermal stability as compared with untreated fiber. The results indicated that the composites prepared with 30wt % of sisal had the highest sound absorption as compared with other composites. Evidence of the successful reaction of sodium hydroxide and heat treatment of the sisal fibers was provided by the infrared spectrum and implied by decreased bands at certain wavenumbers. Observations based on scanning electron microscopy of the fracture surface of the composites showed the effect of alkaline and heat treatment on the fiber surface and improved fiber-matrix adhesion.